The Development of HOTS Test Instrument of Thermodynamics Law for Senior High School - Yeni Rima Liana; Suharto Linuwih; Sulhadi Sulhadi (Universitas Lambung Mangkurat, 2020)
The main analysis in developing assessment instruments is reliability and validity. A validity test is carried out to determine the appropriateness instrument that will be developed, both construction validity and content validity. The reliability test is to determine the level of consistency of the instrument that has been developed. This research was conducted to develop the HOTS ability to test items for high school students. The grid test instruments are arranged based on competence and HOTS indicators, which are then used to arrange items. The test instrument consisted of ten question items relating to the HOTS Thermodynamic Law problem, which included: 1) analyzing the magnitude of engine efficiency, work, heat, and internal energy changes, 2) evaluating Carnot's efficiency, and 3) creating a heat engine. The assessment of the instrument HOTS test obtained Aiken's V score in the range of 0.83 to 0.94, which is in the valid criteria. The validated instrument was piloted in 141 science grade XI student in High School 2 Batang, at Batang Regency, Central Java. The level difficulty of the Polytomous data was analyzed using the QUEST program for classical analysis and PARSCALE 4 for modern analytical theory based on the Partial Credit Model (PCM). The results of data analysis of the experimental items show that of the ten-question items, all are compatible with PCM. The reliability of the test instrument is 0.84, and the item difficulty level is in the range of 0.83 to 1.22. Information functions and Standard Error Measurement (SEM) indicate that test questions developed reliably to measure HOTS students' ability with an average category in -1.9 <θ <+1.7 logit scale with SEM ± 0.5.